Interactive E-Book Colligative Properties of Solutions: Connecting Science and Society in Chemistry Learning - Munawwarah; Muhammad Anwar; Alimin (Postgraduate, University of Mataram, 2024)
This study presents the development of an interactive e-book on the colligative properties of solutions in chemistry. The primary objective of this e-book is to enhance student engagement and understanding by integrating socio-scientific issues (SSI) to connect the material with everyday topics. The development methodology followed Borg and Gall's research and development approach, limited to the fifth stage, which is the main product revision. Validation instruments included both content validation and media validation. Interactive aspects of the e-book feature links in the table of contents, video displays, and a comprehensive presentation of questions complete with scores and solutions in the practice and competency test sections. Content validation results indicated that the e-book is valid, while media validation results placed it in the highly valid category. The incorporation of SSI aims to provide a relevant and engaging learning experience for students.